Students’ Perspectives on the Use of Padlet as a Digital Platform for Academic Writing in an Indonesian EFL Context - Jonris Tampubolon; Maria Fridolin Naben; Benyamin Kau Abi; Fitra Ramadhan; Eliyah A M Sampetoding (Journal of Applied Linguistics, 2026)
This study explores Indonesian EFL students’ perspectives on the use of Padlet as a digital platform for academic writing. A qualitative approach was employed, combining questionnaires, semi-structured interviews, and analysis of Padlet documents. There were 30 university students who were taking academic writing course involved as subjects of this study. The were selected through purposive sampling. The findings reveal that students perceive Padlet positively, particularly for idea generation, peer learning, motivation, and revision support. Challenges include technical problems, uneven participation, limited peer feedback, and anxiety related to public visibility. The study highlights the pedagogical value of Padlet as a socially mediated, collaborative, and process-oriented tool for academic writing, while   emphasizing the need for careful implementation and instructor guidance. Keywords : Padlet; Digital Platform; Academic Writing; EFL Context